2022
DOI: 10.3390/antiox11050862
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Hinders the Protective Effect of Selenite Supplementation on Insulin Signaling

Abstract: The intake of high-fat diets (HFDs) containing large amounts of saturated long-chain fatty acids leads to obesity, oxidative stress, inflammation, and insulin resistance. The trace element selenium, as a crucial part of antioxidative selenoproteins, can protect against the development of diet-induced insulin resistance in white adipose tissue (WAT) by increasing glutathione peroxidase 3 (GPx3) and insulin receptor (IR) expression. Whether selenite (Se) can attenuate insulin resistance in established lipotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, it is not enough since the adipogenesis process is stopped and hyperglycemia further appears. According to these results, in a recent multidisciplinary study, in vivo selenite vs. in vitro selenite supplementation have been found to show different effects on WAT-insulin sensitivity during obesity and highfat diet exposure [78]. In this case, in vitro selenite supplementation protects against IR in 3T3-L1 preadipocytes, despite in vivo studies in mice showing no selenite-induced improvement in insulin sensitivity, with only a modest effect on adipocyte morphology and enhanced insulin production in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not enough since the adipogenesis process is stopped and hyperglycemia further appears. According to these results, in a recent multidisciplinary study, in vivo selenite vs. in vitro selenite supplementation have been found to show different effects on WAT-insulin sensitivity during obesity and highfat diet exposure [78]. In this case, in vitro selenite supplementation protects against IR in 3T3-L1 preadipocytes, despite in vivo studies in mice showing no selenite-induced improvement in insulin sensitivity, with only a modest effect on adipocyte morphology and enhanced insulin production in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, rats supplemented with selenite also showed a positive regulation of one selenoprotein, the GPx3, compared to SeNPs-treated rats (Log 2 FC = 0.80). Recent studies have found that selenite treatment increases GPx3 mRNA and protein levels in a dose-dependent manner, enhancing insulin receptor (IRS-1) expression through the activation of the transcription factor Sp1 in different adipocyte cell culture models [ 43 , 44 ]. This improvement in insulin sensitivity increases the differentiation and function of adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…These effects of Se supplementations on WAT main metabolic pathways align with those found in oxidative balance. In this context, selenite treatment, which inhibits lipolysis and enhances growth signaling, upregulated the genes associated to the antioxidant enzyme GPx3, which improves the insulin signaling process contributing to avoid lipolysis [ 44 ]. It also increased the gene which encoded COX-1, an important modulator of growth pathways [ 45 ] and a promoter of adipogenesis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%